Pengaruh Pemberian Pupuk Kandang Ayam Dan Pupuk KCl Terhadap Pertumbuhan Dan Hasil Tanaman Bawang Merah (Allium ascalonicum,L) - Kristina Frisna Jahung; I Gusti Bagus Udayana; Anak Agung Ngurah Mayun Wirajaya (GEMA AGRO, 2022)
This thesis is entitled "The Effect of Applying Chicken Manure and KCl Fertilizer on the Growth and Yield of Shallot Plants (Allium ascalonicum, L.) "This study aims to determine the effect of doses of chicken manure and KCl fertilizer and their interactions on the growth and yield of onion plants. This research was conducted in the greenhouse of the Faculty of Agriculture, Warmadewa University, Jl Terompong Tanjung Bungkak, Denpasar with an altitude of 25 m above sea level. The research starts from March to June 2022. The design used in this study was a factorial randomized group design (RAK) consisting of 2 factors, namely: the first factor is the dose of chicken manure (A) which consists of 4 treatment levels, namely A 0 = 0 tons ha-1, A1 = 15 tons ha-1, A2 = 30 tons ha-1, A3 = 45 tons ha-1. While the second factor is the dose of KCl (K) fertilizer which consists of 4 levels of treatment, namely K 0 = 0 kg ha-1, K1 = 200 kg ha-1, K2 = 400 kg ha-1, K3 = 600 kg ha-1. The observed variables were maximum plant height, number of leaves, number of tubers per clump, fresh weight of tubers per clump, fresh weight of plots per clump, dry weight of tuber ovens per clump, dry weight of beaver ovens per clump, and harvest index. The results of this study showed that the treatment of chicken manure doses (A) and KCl (K) fertilizer doses and interactions (AxK) differed unreally (Pâ‰¥0.05) against all variables observed plant height (cm), number of leaves (strands), number of tubers per clump (tuber), fresh weight of tubers per clump (g), fresh weight of brangkasan per clump (g), dry weight of tuber ovens per clump (g), dry weight of the oven per clump (g), and harvest index (%). In the dose treatment of chicken manure (A1) has the highest value in the dry weight of the tuber oven, which is 5.03 grams. Keywords : Shallots, Chicken Manure, KCl